2016
DOI: 10.1016/j.ceb.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Adder and a coarse-grained approach to cell size homeostasis in bacteria

Abstract: Cell size control and homeostasis is a long-standing subject in biology. Recent experimental work provides extensive evidence for a simple, quantitative size homeostasis principle coined adder (as opposed to sizer or timer). The adder principle provides unexpected insights into how bacteria maintain their size without employing a feedback mechanism. We review the genesis of adder and recent cell size homeostasis study on evolutionarily divergent bacterial organisms and beyond. We propose new coarse-grained app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
169
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(179 citation statements)
references
References 56 publications
6
169
0
Order By: Relevance
“…We used time-lapse imaging to measure cell size and cell cycle timing in SSB-GFP M. smegmatis cells. Several studies recently developed a division adder model (also called an incremental model) of cell size control, in which bacteria add a constant length (Δ l bd ) from birth to division regardless of birth size (Figures 2A, S2D&S4; STAR Methods) [6, 8, 2023]. Because Δ l bd is not correlated to birth length, we found that M. smegmatis is consistent with this aspect of the division adder model (Figure 2B) [4, 6, 19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used time-lapse imaging to measure cell size and cell cycle timing in SSB-GFP M. smegmatis cells. Several studies recently developed a division adder model (also called an incremental model) of cell size control, in which bacteria add a constant length (Δ l bd ) from birth to division regardless of birth size (Figures 2A, S2D&S4; STAR Methods) [6, 8, 2023]. Because Δ l bd is not correlated to birth length, we found that M. smegmatis is consistent with this aspect of the division adder model (Figure 2B) [4, 6, 19].…”
Section: Resultsmentioning
confidence: 99%
“…Mycobacteria elongate and divide asymmetrically, giving rise to significant variation in cell size and elongation rate among closely related cells [4, 5]. Given the physical asymmetry of mycobacteria, the models that describe coordination of cellular organization and cell cycle progression in model bacteria are not directly translatable [1, 2, 68]. Here we used time-lapse microscopy and fluorescent reporters of DNA replication and chromosome positioning to examine the coordination of growth, division, and chromosome dynamics at a single-cell level in Mycobacterium smegmatis ( M. smegmatis ) and Mycobacterium bovis Bacillus Calmette–Guérin (BCG).…”
mentioning
confidence: 99%
“…A phenomenological linear relation between birth and division size has been observed in experiments [9,15,28] …”
Section: Comparison Of Cell Size Distributionsmentioning
confidence: 99%
“…A possible strategy for such a control, called a sizer, is to set a stochastic threshold. Many microbes, however, rather grow by a constant size from birth to division, called the adder control [3,[13][14][15]. Other mixed strategies may be described by sizer-or timer-like controls [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The same phenomenon was also observed by the Jun group using a similar device that trapped single bacterial cells in tiny channels. [22][23][24] the oscillating behavior in cell size and gene expressions, which indicated a feedback mechanism in cell size control. [25] Combining fluorescent microscopy to a "mother machine" device, the Elf group pushed real-time observation precision to the sub-cellular level.…”
Section: High Resolutionmentioning
confidence: 99%